PENERAPAN PEMBELAJARAN KONSTRUKTIVISME UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA SMP - Evi Sri Rizky; Luvy Sylviana Zanthy (Journal on Education, 2019)
This research is a classroom action research. The aim is to examine the influence of the constructivism approach on the ability of mathematical research in junior high school students. This research was conducted on students of class VII-D at SMP Negeri 5 Cimahi in the odd semester of the 2018/2019 academic year with 34 students. The instrument used was a test of mathematical reasoning ability. The procedure of this study consists of: (1) Planning; (2) Implementation of Actions; (3) Observation and Evaluation; and (4) Reflection. The results of the study on the pretest value on average were 23.68, and the average post-test score was 72.50. The completeness of the learning scenario carried out by the teacher in the first cycle reached 70% and in the second cycle the scenario of learning carried out by the teacher almost reached 90%. Based on the whole, it was concluded that the results of students' mathematical reasoning using constructivism learning were good, which indicated that constructivism approach had an effect on learning in class VII-D in SMP Negeri 5 Cimahi.